Smoking, all-cause, and cause-specific mortality in individuals with diabetes in Mexico: an analysis of the Mexico city prospective study - Daniel Ramírez-García; Carlos A. Fermín-Martínez; Paulina Sánchez-Castro; Alejandra Núñez-Luna; Martín Roberto Basile-Alvarez; Luisa Fernández-Chirino; Arsenio Vargas-Vázquez; Juan Pablo Díaz-Sánchez; Ashuin Kammar-García; Paloma Almeda-Valdés; Jaime Berumen-Campos; Pablo Kuri-Morales; et al. (BMC, 2024)
Abstract Objective Evidence from low- and middle-income countries regarding the effect of smoking in people with diabetes is lacking. Here, we report the association of smoking with mortality in a large cohort of Mexican adults with diabetes. Methods Participants with diabetes mellitus (self-reported diagnosis, use of antidiabetic medications or HbA1c ≥ 6.5%) aged 35-74 years when recruited into the Mexico City Prospective Study were included. Cox regression confounder-adjusted mortality rate ratios (RRs) associated with baseline smoking status were estimated. Results Among 15,975 women and 8225 men aged 35-74 years with diabetes but no other comorbidities at recruitment, 2498 (16%) women and 2875 (35%) men reported former smoking and 2753 (17%) women, and 3796 (46%) men reported current smoking. During a median of 17 years of follow-up there were 5087 deaths at ages 35-74 years. Compared with never smoking, all-cause mortality RR was 1.08 (95%CI 1.01-1.17) for former smoking, 1.11 (95%CI 1.03-1.20) for current smoking, 1.09 (95%CI 0.99-1.20) for non-daily smoking, 1.06 (95%CI 0.96-1.16) for smoking < 10 cigarettes/day (median during follow-up 4 cigarettes/day), and 1.28 (95% CI 1.14-1.43) for smoking ≥ 10 cigarettes/day (median during follow-up 15 cigarettes/day). Mortality risk among daily smokers was greatest for COPD, lung cancer, cardiovascular diseases, and acute diabetic complications. Conclusion In this cohort of Mexican adults with diabetes, low-intensity daily smoking was associated with increased mortality, despite observing smoking patterns which are different from other populations, and over 5% of total deaths were associated with smoking.